2005
DOI: 10.1002/art.21423
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous development of synovitis and cartilage degeneration in transgenic mice overexpressing cathepsin K

Abstract: Objective. Several recent studies have demonstrated that cathepsin K, a proteolytic enzyme capable of degrading native fibrillar collagen, is overexpressed in osteoarthritic cartilage and inflamed synovial tissue. However, it is not known whether increased cathepsin K production is a primary or a secondary event in these diseases. The availability of transgenic UTU17 mice, which exhibit constitutive overexpression of the cathepsin K gene, prompted us to study possible arthritic changes in their knee joints.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 14 publications
3
45
0
1
Order By: Relevance
“…Morko et al, mentioned that overexpression of cathepsin K leads to spontaneous synovitis and cartilage erosion in RA [51].…”
Section: Discussionmentioning
confidence: 99%
“…Morko et al, mentioned that overexpression of cathepsin K leads to spontaneous synovitis and cartilage erosion in RA [51].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, chronic synovial pathology has been detected after OA induction by meniscectomy in an ovine model 17 . In addition, intra articular injections of transforming growth factor (TGF)-b induced synovial hyperplasia and osteophyte formation in a mouse model 18 , and a transgenic mouse model overexpressing cathepsin K spontaneously developed synovitis 19 . We have recently demonstrated that PTH reduced knee-cartilage damage mainly by improving subchondral bone quality in a rabbit model of combined OA and osteoporosis (OP) 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In a dog osteoarthritis model, a potent inhibitor of cathepsin K (SB-55348) decreased the overall tibial degeneration score by 21% and the cartilage degradation score by 32% [105]. In contrast, overexpression of cathepsin K in mice showed increased cathepsin K expression in chondrocytes and led to the spontaneous development of synovitis and cartilage degradation [98,106]. However, the role of cathepsin K in arthritic diseases is not undisputed.…”
Section: Cathepsins In Joint Erosionmentioning
confidence: 91%